PENGARUH KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KEBIJAKAN UTANG PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BEI TAHUN 2009 S/D 2013 - Nurul Annisa Zulmi; Makhdalena '; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aimed to investigate the effect of managerial ownership and institutional ownership of the debt policy. The population in this study are all manufacturing companies listed in the Indonesian Stock Exchange that have data (managerial ownership, institutional ownership and debt policy) consecutive years (2009 until 2013). The data obtained from Indonesian Capital Market Directory (ICMD) researched each company. The data analysis technique used in this research is multiple linear regression. These results indicate that managerial ownership and institutional ownership simultaneously affect the debt policy. While partially, managerial ownership and institutional ownership negatively affect debt policy.Keywords: Managerial Ownership, Institutional Ownership and Debt Policy